Commercial banks as underwriters: implications for the going public process - Puri, Manju (Journal of Financial Economics, 1999)
Commercial bank entry into securities underwriting can affect underwriter behavior because, unlike investment houses, banks also lend to firms. This raises several issues. Are banks better certifiers of firms’ securities than investment houses? If banks hold equity in firms rather than debt, does this make certification more credible? Would one type of underwriter drive out the other? This paper provides a model for analyzing such issues, and derives several interesting results. First, banks, as lenders to firms, can actually be better certifiers than investment houses. Second, equity holding can hinder banks’ certification ability. Finally, banks and investment houses can co-exist.